Sosialisasi Media Informasi Kebutuhan Gizi Harian Pada Unit Pelaksana Teknis (UPT) Puskesmas Mandomai - Sam'ani .; Ferdiyani Haris; Mochammad Ichsan; Muhammad Haris Qamaruzzaman (Universitas Bakti Tunas Husada, 2023)
In serving the local community, the Mandomai Health Center Technical Implementation Unit (UPT) does not only handle the treatment of sick people, but also usually handles complaints from people who are malnourished. All types of food contain different composition of nutrients. The human body will experience malnutrition if it consumes less nutritious food. It is very important to choose a variety of foods according to the body's nutritional needs so that you do not experience a deficiency or excess of nutrients which can cause various diseases, such as malnutrition, obesity, hypertension, diabetes, and other diseases. In order to help the UPT staff at the Mandomai Health Center and the surrounding community in understanding the calculation of nutritional needs and recommendations for a balanced diet, an information application will be disseminated, especially one based on Android mobile in the form of a system that will present information on daily nutritional needs, namely Media Information on Daily Nutritional Needs which will be socialized to UPT Puskesmas Mandomai staff and the surrounding community.